Answer:
6 and 18
Step-by-step explanation:
a+b=24
5a-b=12
5a+a=6a
24+12=36
6a=36 so A on it's own is 6
24-6=b
b=18
hope this helps!
Answer:
NEED HELP PLEASE!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Explain the converse of the Pythagorean theorem.
A.
The converse of the Pythagorean theorem states that if a triangle is a right triangle, then the sum of the squares of its legs is less than the square of its hypotenuse.
<u>B. </u>
<u>The converse of the Pythagorean theorem states that if the square of one side of a triangle is equal to the sum of the squares of the other two sides, then the triangle is a right triangle.
</u>
C.
The converse of the Pythagorean theorem states that if a triangle is a right triangle, then the sum of the squares of its legs is greater than the square of its hypotenuse.
D.
The converse of the Pythagorean theorem states that if the square of one side of a triangle is greater than the sum of the squares of the other two sides, then the triangle is a right triangle.
Step-by-step explanation:
7+3t -t
------- = ----- is the relevant equation here. We don't ask, "What is 7+3t over
4 8 -t over 8," but rather "Solve the following equation for t."
Cross multiplying, 56 + 24t = -4t
-56
Then: 28t = 56, and t = ------ = -2 (answer)
28
The solution to "<span>What is 7+3t over 4 = -t over 8" is t = -2.</span>
Answer:
A=8x-8
B=5x+25
A=B(BEING corresponding angles)
8x-8=5x+25
8x-5x=25+8
3x=33
x=33/3
x=11
now 8x-8= 8×11-8
= 88-8
=80
5x+25= 5×11+25
=55+25
= 80
A=B#
Answer:
I'm not 100% sure, but I think it's 3